2016
DOI: 10.1186/s12906-016-1433-1
|View full text |Cite
|
Sign up to set email alerts
|

Reno-protective effect and mechanism study of Huang Lian Jie Du Decoction on lupus nephritis MRL/lpr mice

Abstract: BackgroundHuang Lian Jie Du Decoction (HLJDD), a very famous traditional Chinese medicinal prescription, has been used for heat dissipation and detoxification in China. This study was aimed to evaluate the reno-protective effects of HLJDD against lupus nephritis (LN) in vivo in MRL/lpr mice.MethodsAnimals were administered orally every day for eight consecutive weeks except the mice of normal group and model group. Organ indexes, serum interleukin-6 (IL-6), interleukin-10 (IL-10), interferon-gamma (IFN-γ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…The data of the present study indicated that increases in inflammatory and anti-inflammatory factors increased with the occurrence of the inflammatory response. Similar results have been observed for other autoimmune diseases (24).…”
Section: Discussionsupporting
confidence: 90%
“…The data of the present study indicated that increases in inflammatory and anti-inflammatory factors increased with the occurrence of the inflammatory response. Similar results have been observed for other autoimmune diseases (24).…”
Section: Discussionsupporting
confidence: 90%
“…The medicinal ingredients of QED recipe were purchased from Sanjiu Medical and Pharmaceutical Groups (Shenzheng, China), and carefully authenticated by colleagues in Department of Pharmacology of Third military medical university (Chongqing, China). The mixture was decocted twice by refluxing with water (1:10 and then 1:5 w/v) for 30 min, the drug suspension was lyophilized, and subjected to High Performance Liquid Chromatography fingerprinting 35 . Drug powder was dissolved in normal saline to a final concentration of 1.8 g/mL (equivalent to the dry weight of the raw materials).…”
Section: Methodsmentioning
confidence: 99%
“…It has a wide range of pharmacological activities (e.g., antibacterial, anti-inflammatory, antioxidant, and neuroprotective activities) and multiple functions (e.g., antiendotoxin, anticoagulation, immunomodulatory, anti-inflammatory, and antiviral functions). It effectively improves the hypoxia–ischemia resistance of tissues and organs and endothelium-dependent vasodilation, reduces creatinine levels, and inhibits the expression of angiotensin II and inflammatory cytokines, thereby effectively protecting the renal function of patients ( Lu et al, 2011 ; Yi et al, 2012 ; Khan et al, 2016 ; Kumar et al, 2016 ; Li et al, 2016 ; Nie et al, 2016 ). In LN, experiments confirmed that HLJDD reduced urine protein concentration and creatinine concentration, alleviated renal lesions, improved renal function, and decreased the mortality rate of an LN mouse model.…”
Section: Traditional Chinese Medicine Preparations In Lupus Nephritismentioning
confidence: 99%
“…Recent studies have reported that many TCM Preparations and Monomers and extracts of these drugs have significant efficacy in the treatment of immune diseases, such as the classic formula Huang-Lian Jie-Du decoction (HLJDD), which has unique clinical efficacy in the treatment of immune diseases such as lupus nephritis, rheumatoid arthritis, and ulcerative colitis. Nie et al (2016) found that HLJDD significantly inhibited STAT3 phosphorylation and thus exerted renoprotective effects in the treatment of lupus nephritis (LN) mice; Li et al (2021) found that the potential mechanism of HLJDD in the treatment of RA may be attributed to the inhibition of immune inflammatory response, reduction of chemokine release, and attenuating the destruction of extracellular matrix (ECM) in the synovial compartment; Yuan et al (2020) suggesting that HLJDD improves acute ulcerative colitis in mice by modulating NF-κB and Nrf2 signaling pathways and enhancing intestinal barrier function.…”
Section: Introductionmentioning
confidence: 99%